Sikap Perempuan Dalam Ibadah Berdasarkan I Timotius - Julen Makanata (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2018)
Julens Makanta, The Attitudes of Women in Worship Based on 1 Timothy. The attitude of women in worship becomes the main focus of various parties who are pro and contra. The study of women's attitudes in worship in 1 Timothy 2: 8-15 is expected to be a contribution to the churches that continue to interpret the Bible lanklek and discriminate against women to take an active role in worship, even in Christian organizations in which women play a broad role. In addition to contributing to other churches and Christian organizations, this study is also expected to provide an understanding that should not women's attitudes in worship be restrained. Both women and men are equally the equal of God's creations, complementary and have their own craftsmanship and creativity. Julens Makanata, Sikap Perempuan Dalam Ibadah Berdasarkan 1 Timotius. Sikap perem-puan dalam ibadah menjadi sorotan utama dari berbagai pihak yang pro dan kontra. Studi tentang sikap perempuan dalam ibadahdalam surat 1 Timotius 2:8-15 ini diharapkan dapat menjadi kontribusi bagi gereja-gereja yang masih terus menafsirkan Alkitab secara leterlek dan mendiskriminasi kaum perempuan untuk berperan aktif dalam ibadah, bahkan dalam organisasi-organisasi Kristen yang di dalamnya para wanita berperan secara luas. Selain dapat memberikan kontribusi bagi gereja-gereja dan organisasi Kristen lainnya, studi ini juga diharapkan dapat memberikan pemahaman bahwa tidak seharusnya sikap perempuan dalam ibadah dikekang. Baik perempuan maupun laki-laki adalah sama-sama ciptaan Allah yang sepadan, saling melengkapi dan memiliki keahlian dan kreativitasnya masing-masing.